(3cJGH GdESJNQGL dCMcGe GdNQGLs - (3GHf GdeLOj , TgGH GdOjf CHh GdYHGS Hf GdeLOj,J (B850 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi egO dHfi GOe bHd Gf jNda HYVge ajgG dHYV CeG HYO aEf Gddg JYGdi Ndb GdNdb cdge dYHGOJg ceG bGd (B" (3heG NdbJ GdLf hGdGfS EdG djYHOhfi (B" s
(3BNQgG (B:s
(3hBNQ GdQhGjI JOd Ydi Gfg Ef CNP efg HSHH GdNQGL GMJSH Hg ef GdYTQ hEf CNP efg HSHH BNQ ZjQ GdNQGL ef ehJ GdGQV hfMhgG de jMJSH ajfab MjfFmP QhGjI MQH GdSGHbI hGddg SHMGfg hJYGdi CYde s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3HChdgG JedcGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B125 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B221s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdESdGejs